Crystallization and X‐ray diffraction studies of a complete bacterial fatty‐acid synthase type I. Issue 11 (1st November 2015) - Enderle, Mathias; McCarthy, Andrew; Paithankar, Karthik Shivaji; Grininger, Martin
Abstract : While a deep understanding of the fungal and mammalian multi‐enzyme type I fatty‐acid synthases (FAS I) has been achieved in recent years, the bacterial FAS I family, which is narrowly distributed within the Actinomycetales genera Mycobacterium, Corynebacterium and Nocardia, is still poorly understood. This is of particular relevance for two reasons: (i) although homologous to fungal FAS I, cryo‐electron microscopic studies have shown that bacterial FAS I has unique structural and functional properties, and (ii) M. tuberculosis FAS I is a drug target for the therapeutic treatment of tuberculosis (TB) and therefore is of extraordinary importance as a drug target. Crystals of FAS I from C. efficiens, a homologue of M. tuberculosis FAS I, were produced and diffracted X‐rays to about 4.5 Å resolution.